Clinical parameters to predict adverse outcomes in patients with shunt-dependent physiology with a Blalock-Taussig-Thomas shunt - Saloni P Shah; Rohit S Loomba (Wolters Kluwer Medknow Publications, 2023)
In patients with shunt-dependent physiology, early risk factor identification can facilitate the prevention of adverse outcomes. This study aims to determine a scoring system to estimate the risk for adverse outcomes after Blalock-Taussig-Thomas shunt placement. Of the 39 neonates with Blalock-Taussig-Thomas shunt placement, 10 experienced the composite outcome. The resulting risk score from clinical and hemodynamic variables attributed 1 point for each of the following: central venous pressure >7.8, serum lactate >1.8 mmol/L, renal oxygen extraction ratio >32, and vasoactive-inotrope score >8.7. A score of 0 was associated with a 0% risk of the composite outcome, a score of 1 or 2 with a 15% risk, and a score of 3 or 4 with a 60% risk. A combination of increased central venous pressure, increased serum lactate, increased renal oxygen extraction ratio, and increased vasoactive-inotrope score are highly accurately associated with the risk of cardiopulmonary arrest, need for extracorporeal membrane oxygenation, or inpatient mortality after a Blalock-Taussig-Thomas shunt in patients with shunt-dependent physiology.